PHENOLOGY AND GROWTH OF THE PHYSIC NUT IN THE FLOREST ZONE OF THE STATE OF ALAGOAS, BRAZIL - SANTOS, Claudiana Moura dos; ENDRES, Laurício; WANDERLEY FILHO, Humberto Cristiano de Lins; ROLIM, Eduardo Vicente; FERREIRA, Vilma Marques (Scientia Agraria, 2010)
The physic nut (Jatropha curcas L.), pertains to the Euphorbiaceae family, is a native plant of Americas and naturalised throughout tropical America, Asia and Africa. Part of the interest for the cultivation of this species is related to the use of the seeds for oil production for the obtainment of the bio-diesel. This work had as objective to characterize the phenologic behavior of the physic nut for the city of Rio Largo, Alagoas. Some growth and phenologic observations were taken during the period of September 2006 to December 2007 in plants located in an experimental field, in the Center of Agrarian Sciences of the Federal University of Alagoas, in the city of Rio Largo. Some records on growth were taken biweekly on 50 plants, and weekly on leaf fall and sproutings, budding and fruiting on 20 plants. Twenty plants were also observed for counting (the number of inflorescence per plant, the number of flower buttons per plant, the number of flowers per plant and the number of fruits per plant) and 10 plants to observe the development of the fruit. The Physic nut presented vegetative growth with pattern seasonal; slow growth was verified during the dry season, and accelerated growth during the rainy season. The leaf fall initiated during the end of the rainy season and continued through the dry season, where some plants entered into dormancy. A budding and fruiting peak was verified during the rainy season. This study suggests that the vegetative and reproductive events of the physic nut showed themselves as seasonal, concentrating on a more intense way its phenological activities during the rainy season.